Efektivitas Macromedia Flash-8 pada Pembelajaran Pendidikan Pancasila di Kelas IV Sekolah Dasar - Zulfajri, Aldefrigo; Reinita, Reinita (Universitas Negeri Padang, 2024)
This research is based on the importance of innovation in learning at the elementary school level to improve the quality of learning. This research aims to produce valid, practical, and effective learning media using the Macromedia Flash 8 application in learning Pancasila Education in grade IV Elementary School. The type of research used is Research and Development (R&D) with the ADDIE development model (analysis, design, development, implementation, and evaluation). The research subjects were fourth grade teachers and students at SDN 16 Padang Besi. Data collection techniques were observation and interview. The research instruments used validity, practicality, and effectiveness tests. The development of learning media obtained validity results of 95.87% with a valid category. the results of practicality get a score of 95.83 by teachers and a score of 92.56% by students with a practical category. Effective results using N-Gain obtained a score of 67.18% in the moderate category. Based on the results of the research that has been done, it can be concluded that the development of learning media using the Macromedia Flash 8 application has been valid, practical, and effective in learning Pancasila Education in grade IV Elementary School. The learning media developed can be an alternative learning media solution that is innovative and interesting for students in learning learning learning materials.